Etika dan Profesionalisme Guru PAK dalam Membentuk Karakter Disiplin Siswa - Dewi Clara Simanjuntak; Dorlan Naibaho (Tri Tunggal: Jurnal Pendidikan Kristen dan Katolik, 2025)
Discipline is one of the parts included in the implementation of the Indonesian student profile. To create a golden and superior Indonesia, of course the nation's children as the next generation must be equipped as well as possible, including in terms of education. Student discipline has experienced a decline, both discipline at home, discipline at school, and especially discipline in the community. Many school children often go to school late, are often reckless on the street, often wander around at night, rarely pray, and have other bad behavior. This shows that student ethics and discipline have experienced a significant decline, which if left unchecked will definitely hinder the realization of a golden and superior Indonesia. That is why as an educator, a PAK teacher must be able to guide the nation's future young generation to live ethically and disciplined lives. With the ethics and professionalism possessed by PAK teachers, it is hoped that more and more students will live disciplined and civilized lives.